A rare case of isolated sigmoid colon injury in blunt trauma abdomen: a case report - Kopperundevi, V.; Vimla, G.; Vyshnavi Y., Sai; Kannan, R. (International Surgery Journal, 2022)
Isolated colonic injury due to blunt abdominal trauma is very rare. Modalities of detecting colonic injuries are also very inconclusive in the background of a blunt trauma abdomen. Here we present a case of blunt trauma abdomen in a 45 year old male who sustained steering wheel injury in a road traffic accident 5 days ago and presented with symptoms and signs of peritonitis. Ultrasonography showed free fluid in the pelvis that was confirmed by contrast enhanced CT of the abdomen which revealed additional intraperitoneal air pockets with hemoperitoneum. Patient was taken up for emergency laparotomy and findings included fecal peritonitis, sigmoid colon perforation with impending transection. Peritoneal lavage with Hatmann’s procedure was done. Due to lack of a definitive diagnostic method, it is very challenging to detect such injuries and this will lead to delay in treatment and subsequently results in high morbidity and mortality.